Supercapacitor with Carbon/MoS2 Composites - Tobis, Maciej; Sroka, Sylwia; Frąckowiak, Elżbieta (Frontiers in Energy Research, 2021)
Transition metal dichalcogenides (TMDs) with a two-dimensional character are promising electrode materials for an electrochemical capacitor (EC) owing to their unique crystallographic structure, available specific surface area, and large variety of compounds. TMDs combine the capacitive and faradaic contribution in the electrochemical response. However, due to the fact that the TMDs have a strong catalytic effect of promoting hydrogen and oxygen evolution reaction (HER and OER), their usage in aqueous ECs is questioned. Our study shows a hydrothermal l-cysteine–assisted synthesis of two composites based on different carbon materials—multiwalled carbon nanotubes (NTs) and carbon black (Black Pearl-BP2000)—on which MoS2 nanolayers were deposited. The samples were subjected to physicochemical characterization such as X-ray diffraction and Raman spectroscopy which proved that the expected materials were obtained. Scanning electron microscopy coupled with electron dispersive spectroscopy (SEM/EDS) as well as transmission electron microscopy images confirmed vertical position of few-layered MoS2 structures deposited on the carbon supports. The synthetized samples were employed as electrode materials in symmetric ECs, and their electrochemical performance was evaluated and compared to their pure carbon supports. Among the composites, NTs/MoS2 demonstrated the best electrochemical metrics considering the conductivity and capacitance (150 Fg−1), whereas BP2000/MoS2 reached 110 Fg−1 at a current load of 0.2 Ag−1. The composites were also employed in a two-electrode cell equipped with an additional reference electrode to monitor the potential range of both electrodes during voltage extension. It has been shown that the active edge sites of MoS2 catalyze the hydrogen evolution, and this limits the EC operational voltage below 1 V. Additional tests with linear sweep voltammetry allowed to determine the operational working voltage for the cells with all materials. It has been proven that the MoS2/carbon composites possess limited operating voltage, that is, comparable to a pure MoS2 material.